Accuracy of imaging modalities at detecting extracapsular spread of cervical lymph node metastases in HPV-associated oropharyngeal cancer: a systematic review protocol of diagnostic test accuracy. Issue 1 (22nd January 2022) - Morey, Tristan; Stern, Cindy; Foreman, Andrew; Hodge, John-Charles
ABSTRACT: Objective: The objective of this review is to evaluate the accuracy of different imaging modalities in detecting extracapsular spread (ECS) of cervical lymph node metastases in human papillomavirus positive (HPV+) oropharyngeal squamous cell carcinoma (OPSCC). Introduction: Extracapsular spread of lymph node metastases is associated with poor prognosis, and its detection in head and neck cancer is crucial for treatment planning. Commonly used imaging modalities to detect ECS in OPSCC include computed tomography, magnetic resonance imaging, positron emission tomography, and ultrasonography. Currently there is no gold standard imaging modality to detect ECS in OPSCC. Inclusion criteria: This review will consider published studies examining the diagnostic accuracy (including sensitivity and specificity) of an imaging modality used to detect ECS in HPV+ OPSCC. Participants will have a diagnosis of HPV+ OPSCC and suspected diagnosis of ECS of cervical lymph node metastases. The index test will be different imaging modalities used to detect ECS, and the reference test will be histopathology. Methods: A three-step search strategy will be undertaken to identify relevant studies in MEDLINE, Embase, Cochrane Central Register of Controlled Trials, Web of Science, and Scopus. A standardized critical appraisal tool (QUADAS-2) will be used to assess the methodological quality of the studies. The main outcomes will be sensitivity and specificity measures reported with 95% confidence intervals. Meta-analysis will be conducted using a bivariate model approach after pooling the studies according to imaging modality. Meta-regression will be used to explore heterogeneity. Meta-regression and subgroup analyses will be used to compare studies and imaging modalities. The results will be presented using either paired forest plots, summary receiver operator characteristic curves, or a narrative synthesis. A GRADE Summary of Findings will be provided. Systematic review registration number: PROSPERO CRD42021250626